Elevated serum CYFRA 21‐1 level as a diagnostic marker for thymic carcinoma. Issue 21 (27th September 2021) - Shiiya, Haruhiko; Ujiie, Hideki; Hida, Yasuhiro; Kato, Tatsuya; Kaga, Kichizo; Wakasa, Satoru; Kikuchi, Eiki; Shinagawa, Naofumi; Okada, Kazufumi; Ito, Yoichi M.; Matsuno, Yoshihiro
Abstract: Background: No useful tumor markers have been identified for the diagnosis of thymic carcinomas. Serum cytokeratin 19 fragment, measured using the CYFRA 21‐1 immunoassay, is used as a tumor marker for squamous cell carcinomas in various malignant tumors. Here, we evaluated the value of CYFRA 21‐1 in diagnosing thymic carcinoma. Methods: We retrospectively reviewed 94 patients with pathological diagnoses of thymic carcinoma or thymoma (32 and 62 patients, respectively) who were referred to our departments between January 2000 and March 2019. Primary outcomes included tumor marker levels and their diagnostic accuracy. Results: Patients with thymic carcinoma were significantly more likely to be male (thymic carcinoma, 68.8%; thymoma, 40.3%; p = 0.02), have an advanced TNM stage ( p < 0.01), and a significantly higher CYFRA 21‐1 level than those with thymoma (thymic carcinoma: median = 4.2 ng/ml; interquartile range [IQR] = 2.1–6.1 ng/ml vs. thymoma: median = 1.2 ng/ml; IQR = 0.9–1.7 ng/ml; p < 0.01). Receiver operating characteristic curves demonstrated that the area under the curve for CYFRA 21‐1 to distinguish thymic carcinoma from thymoma was 0.86 (95% confidence interval [CI]: 0.74–0.93; cutoff = 2.7 ng/ml; sensitivity = 68.8%; specificity = 95.2%). Multivariable analysis demonstrated that CYFRA 21‐1 (odds ratio = 25.6; 95% CI: 4.6–141.6; p < 0.01) was an independent predictor for thymic carcinoma after adjusting for TNM stage. Conclusions: Serum CYFRA 21‐1 level may help in diagnosing thymic carcinoma. Abstract : Patients with thymic carcinoma showed higher CYFRA 21‐1 levels than those with thymoma. ROC curve of the CYFRA 21‐1 used to distinguish thymic carcinoma and thymoma demonstrated the AUC for CYFRA 21‐1 of 0.86. Multivariable analysis demonstrated that CYFRA 21‐1 level independently distinguished thymic carcinoma from thymoma.